(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2023)
Bangladesh, being a geographically vulnerable country experiences a variety of severe weather phenomena and most of them occur during the pre-monsoon season (March-May). This study investigates the occurrence of the pre-monsoon extreme weather events in Sunamganj and their impacts on the rice yield. Sunamganj is one of most vulnerable areas of Bangladesh that experiences almost all types of extreme weather phenomena during pre-monsoon and therefore the assessment of the effect of these hazards on rice yield have been conducted in Dakshin Sreepur union, Tahirpur upazila, Sunamganj. This study has been accomplished by blending the findings of climate data analysis with field investigation. About 13 extreme climate indices related to temperature and rainfall created by the Expert Team on Climate Change Detection Indices (ETCCDI) were considered to evaluate the correlation between rice yield and extreme weather events in the particular region. The correlation shows that extreme events are not the only factor influencing the rice yields; rather, a few related factors such as socio-economic context, physiographic settings, river bed siltation, construction and management of dams are also affecting the rice production in the study area. As a result, the solutions derived from farmers are important in reducing the detrimental impact of extreme events on rice yield for effective food production. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 11(1), 2022: 111-130